'Action' on structured freeform surfaces. (16th April 2018) - Whitehouse, David J
Abstract: Surfaces are becoming more complex partly due to the more complicated function required of them and partly due to the introduction of different manufacturing processes. These have thrown into relief the need to consider new ways of measuring and characterizing such surfaces and more importantly to make such characterization more relevant by tying together the geometry and the function more closely. The surfaces which have freeform and structure have been chosen to be a carrier for this investigation because so far there has been little work carried out in this neglected but potentially important area. This necessitates the development of a strategy for their characterization. In this article, some ways have been found of identifying possible strategies for tackling this characterization problem but also linking this characterization to performance and manufacture, based in part on the principles of least action and on the way that nature has evolved to solve the marriage of flexible freeform geometry, structure and function. Recommendations are made for the most suitable surface parameter to use which satisfies the requirement for characterizing structured freeform surfaces as well as utilizing 'Action' to predict functionality.